Ferritin Level Decreased between the Second and Third Trimester of Pregnancy - Tendean, Hermie MM. (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To know the change in ferritin level in second and third trimester of pregnancy. Methods: This study was a cohort study. The level of ferritin was estimated in the second trimester of pregnancy and examined again in the third trimester of pregnancy. Data processed and analyzed by statistically. Result: The number of sample in this study was 30 patients. From this study, we found that the Ferritin level in second to third trimester of pregnancy was decreased in 28 patients (93.3%) and increased in 2 patients (6.7%). This result showed that ferritin serum level in second and third trimester would significant difference (p < 0.001). This different can be showed in media ferritin serum level in second trimester higher than third trimester (31.10 ng/ml > 22.20 ng/ml). Conclusion: There was a significant decrease in the level of ferritin from the second to third trimester. This could be caused by the occurence of hemodilution reaching its peak at 28-32 weeks of pregnancy, increasing the need of iron intake. This could also be caused by an imbalanced diet of the mother. [Indones J Obstet Gynecol 2013; 37-2: 77-81] Keywords: ferritin, pregnancy